Optimasi Fasilitas Warning Sign Dalam Meningkatkan Pelayanan Penumpang Di Terminal Bandar Udara Internasional Juanda Surabaya - Suprayogi; Awan (Universitas Katolik Widya Karya Malang, 2023)
KM 22 of 2005 describes the application of SNI 03-7094-2005 regarding signs at airport terminals as a mandatory standard which explains that every area within the passenger terminal must be equipped with clear and easy-to-understand warning signs. Obstacles found by researchers when carrying out initial observations were finding deficiencies in installing warning signs at Terminal 1 of Juanda International Airport, Surabaya. The purpose of this study is to find out how to optimize the warning sign facility in improving passenger service at the Juanda International Airport Surabaya terminal, to find out the obstacles faced and the solutions in optimizing the warning sign facility at Juanda International Airport. This study uses a qualitative method. This research was conducted at Juanda International Airport in Surabaya which was held in June 2023. The data collection techniques used were observation, interviews, and documentation. The validity test of the data used is source triangulation and technique triangulation. Data analysis used is data reduction, data presentation, and conclusions. The results of research based on service indicators show that: (1) physical evidence (tangibles) includes an imbalance in the placement of signboards; (2) reliability includes the use of available tools and the application of clear service standards; (3) responsiveness, including responsiveness to complaints and input from passengers; (4) guarantee (assurance) includes routine maintenance, as well as providing accurate information; (5) empathy (empathy) includes providing individual and responsive services. The obstacles encountered are that the warning sign is only visible from the west side of the terminal area, but not visible from the east side, the placement of the no smoking sign is not optimal, the no smoking sign is damaged, there are instructions for using a hydrant box that is less strategic .